2022
DOI: 10.3389/fnut.2022.978475
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene and cardiovascular diseases: An overview of pre-clinical studies focused on the underlying molecular mechanism

Abstract: Benzo(a)pyrene (BaP) is a highly toxic and carcinogenic polycyclic aromatic hydrocarbon (PAH) whose toxicological effects in the vessel-wall cells have been recognized. Many lines of evidence suggest that tobacco smoking and foodborne BaP exposure play a pivotal role in the dysfunctions of vessel-wall cells, such as vascular endothelial cell and vascular smooth muscle cells, which contribute to the formation and worsening of cardiovascular diseases (CVDs). To clarify the underlying molecular mechanism of BaP-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…In the past years, the exposure to polycyclic aromatic hydrocarbons (PAHs), more specifically to benzo(a)pyrene (BaP), is more common than ever before [ 15 ]. BaP is a crystalline, aromatic hydrocarbon that consists of five fused benzene rings and is formed during the incomplete combustion or pyrolysis of organic matter [ 16 ]. It is primarily found in gasoline and diesel engine exhaust, petroleum asphalt, charcoal-broiled foods, amino acids, fatty acids, and carbohydrate pyrolysis products, among others [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, the exposure to polycyclic aromatic hydrocarbons (PAHs), more specifically to benzo(a)pyrene (BaP), is more common than ever before [ 15 ]. BaP is a crystalline, aromatic hydrocarbon that consists of five fused benzene rings and is formed during the incomplete combustion or pyrolysis of organic matter [ 16 ]. It is primarily found in gasoline and diesel engine exhaust, petroleum asphalt, charcoal-broiled foods, amino acids, fatty acids, and carbohydrate pyrolysis products, among others [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on specific feature genes linked to AAA have been published. AHR and its associated signal transduction system are primarily responsible for the inflammatory response, oxidative stress, as well as genetic toxicity of vessel-wall cells 43 . Apelin and its cognate G protein-coupled receptor APLNR constitute a signaling pathway with a positive inotropic effect on cardiac function and a vasodepressor function in the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is a major source of PAH for the general population (2). Benzo(a)pyrene (BaP), a PAH present in tobacco smoke, has been suggested as the cause of human diseases, including cancers and cardiovascular diseases (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that BaP causes the progression of atherosclerosis, the underlying mechanism remains unclear. Many studies have focused on how BaP exposure can affect the atherosclerotic process (3,(6)(7)(8)(9). Benzo(a)pyrene is a strong aryl hydrocarbon receptor agonist (AhR).…”
Section: Introductionmentioning
confidence: 99%